Multivectorial strategy to interpret a resistive behaviour of loads in smart buildings - Castilla, Manuel V.; Bravo, Juan C.; Martín, Francisco I. (My University, 2018)
In Smart buildings, electric loads are affected by an important distortion in the current and voltage waveforms, caused by the increasing proliferation of non linear electronic devices. This paper presents an approach on non sinusoidal power theory based on Geometric Algebra that clearly improves traditional methods in the optimization of apparent power and power factor compensation. An example is included that demonstrates the superiority of this approach compared with traditional methods.
Keywords: Ingeniería eléctrica - Matemáticas; Building loads; Geometric algebra (GA); Multivector; Resistive loads